The Influence Of The Implementation Of Green Accounting And Corporate Social Responsibility Based On Tri Hitakarana On Financial Performance - Luh Putu Widi Laksmi; Komang Adi Kurniawan Saputra; I Dewa Ayu Eka Pertiwi (WICAKSANA: Jurnal Lingkungan dan Pembangunan, 2024)
This study aims to test and analyze the effect of the implementation of green accounting and corporate social responsibility based on tri hita karana on financial performance in the hotel sector. This study was conducted in the hotel sector throughout Gianyar Regency with a research sample of 90 respondents taken using purposive sampling techniques. All data obtained from the questionnaire distribution were suitable for use, then analyzed using multiple linear regression, and hypothesis testing (t-test and f-test). The results of the study showed that the implementation of green accounting had a positive and significant effect on financial performance in the hotel sector throughout Gianyar Regency. Implementing green accounting in the company, it will be able to improve the company's financial performance, one of which is by including environmental raw material costs in the company's accounting reports. Corporate social responsibility based on tri hita karana has a positive and significant effect on financial performance in the hotel sector throughout Gianyar Regency. By implementing Corporate Social Responsibility based on Tri Hita Karana, the company will be able to gain the trust of the community around the company, so that the surrounding community can accept the existence of the company and prevent external conflicts with the surrounding community, which in the end can help the company to be accepted legally and not incur external costs that can affect the company's financial performance.